1998
DOI: 10.1145/278298.278303
|View full text |Cite
|
Sign up to set email alerts
|

Efficient descriptor-vector multiplications in stochastic automata networks

Abstract: This paper examines numerical issues in computing solutions to networks of stochastic automata. It is well-known that when the matrices that represent the automata contain only constant values, the cost of performing the operation basic to all iterative solution methods, that of matrix-vector multiply, is given by ρ N = Π N i-1 n i × Σ N i=1 n i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
203
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(206 citation statements)
references
References 12 publications
0
203
0
3
Order By: Relevance
“…Second, the space required to store the description of components is in general much smaller than the explicit list of transitions, even in a sparse representation. However, using this representation instead of the usual sparse matrix form increases the time required for numerical analysis of the chains [6,15,37,33]. Note that we are interested in performance indices R defined as reward functions on the steady-state distribution (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the space required to store the description of components is in general much smaller than the explicit list of transitions, even in a sparse representation. However, using this representation instead of the usual sparse matrix form increases the time required for numerical analysis of the chains [6,15,37,33]. Note that we are interested in performance indices R defined as reward functions on the steady-state distribution (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Despite considerable works [7,12,15,37], the numerical analysis of Markov chains, is still a very difficult problem when the state space is too large or the eigenvalues badly distributed. Fortunately enough, while modeling high speed networks, it is often sufficient to satisfy the requirements for the Quality of Service (QoS) we expect.…”
Section: Introductionmentioning
confidence: 99%
“…In SANs [6,19] and in SGSPNs [18], it has been shown that the transition matrix can be expressed as:…”
Section: The Shuffle Algorithmmentioning
confidence: 99%
“…Therefore, the multiplication of the z in n • k by Q (i) gives z out n • k. A pseudo-code of the E-Sh can be found in [20]. Complexity: The complexity of the algorithm for multiplying a vector and a classic tensor product may be obtained by observing the number of vector-matrix multiplications that are executed [6,19]. If we assume that the matrices Q (i) are stored in a sparse compacted form, and letting nz i denote the number of nonzero elements in the matrix Q (i) , then the complexity of E-Sh is given by…”
Section: The Shuffle Algorithmmentioning
confidence: 99%
See 1 more Smart Citation